Psychotherapy theories and techniques : a reader - Vandenbos, Gary R.; Meidenbauer, Edward; Frank-McNeil, Julia (Washington, DC : American Psychological Association, 2014)
Explores the richness and variety of psychotherapy in a collection of carefully chosen excerpts from APA publications. Intended for students and practitioners, this volume provides a unique look at contemporary psychotherapy theory and the specific interventions associated with each orientation. All major approaches in psychotherapy are included.
How to Use This Book With PsycTHERAPY, APA's Database of Psychotherapy Demonstration Videos
Includes bibliographic references and index.
Keywords: PSYCHOTHERAPY; PSYCHOTHERAPY -- METHODOLOGY; PSYCHOTHERAPY -- PHILOSOPY